Exposure to video games: effects on sleep and on post-sleep cognitive abilities. A sistematic review of experimental evidences - Peracchia, Sara; Curcio, Giuseppe (Sleep Science, 2018)
The public opinion is ever more interested and worried about possible effects of exposure to VGs (video games) on human life and well-being. Scientific literature shows several evidences highlighting negative outcomes on behavioural, emotive, cognitive and physical health spheres. All these aspects are intrinsically linked to sleep quality and quantity and to date very few studies directly investigated the effects of videogame (VG) exposure on sleep and post-sleep cognitive status. The aim of the present systematic review is to examine the impact that the exposure to VGs can produce on sleep pattern and the consequent post-sleep cognitive abilities. To this extent, only studies directly investigating the effects of VGs on sleep features and post-sleep cognitive abilities have been selected and discussed. Data currently present in literature show the alteration of sleep pattern after exposure to VGs. The analysis indicated a reduction of Total Sleep Time (TST) and an increase of Sleep Onset Latency (SOL), modifications of the REM sleep and Slow Wave Sleep (SWS), and increased sleepiness and self-perceived fatigue. Moreover, post-sleep sustained attention and verbal memory also appear to be impaired. It can be concluded that playing VGs for long periods, particularly in the evening, is a significant, common and probable cause of sleep problems: evening exposure to VGs, in fact, can bring to insufficient and low quality sleep, with possible effects on cognition in the subsequent waking days. Potential methodological flaws and limitations of these studies have also been described and discussed. Because of the very limited number of available study on this topic further research is strongly needed.
Keywords: Adolescent; Video Games; Sleep; Disorders of Excessive Somnolence; Memory; Attention